2007
DOI: 10.1179/joc.2007.19.6.658
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects and Risk Factors of NosocomialStenotrophomonas maltophiliaBacteremia Episodes in a Turkish Intensive Care Unit

Abstract: Stenotrophomonas maltophilia is an important nosocomial pathogen with increasing frequency in recent years, especially in immunocompromised and clinically debilitated patients. The aim of this study is to describe the characteristics of 35 episodes of S. maltophilia bacteremia at Celal Bayar University hospital in Turkey over a 3-year period from January 2003 to December 2005. Cases were identified with microbiology laboratory records and clinical data were collected from the medical record of each patient. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Some studies suggest that bacteraemia due to SM was directly influenced by the conditions of each patient [15], [16], [26], [28], [31]. However, other studies have reported that the initial administration of the inappropriate antibacterial treatment to patients was a significant predictor of mortality [5], [17], [18], [32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that bacteraemia due to SM was directly influenced by the conditions of each patient [15], [16], [26], [28], [31]. However, other studies have reported that the initial administration of the inappropriate antibacterial treatment to patients was a significant predictor of mortality [5], [17], [18], [32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Stenotrophomonas maltophilia has multi‐antibiotic resistance because of the natural possession of metallo‐β‐lactamase and cephalosporinase . Community‐acquired S. maltophilia infection is rare; however, under some risk conditions including a compromised health status , indwelling central venous catheter (CVC) or ventilation tube , exposure to broad‐spectrum antibiotics , intensive care unit (ICU) stay , and long‐term hospitalization , S. maltophilia infection can develop as severe bloodstream infection or pneumonia. Several previous studies have shown clinical characteristics and risk factors of S. maltophilia infection in patients with hematologic diseases after chemotherapy and allogeneic hematopoietic stem cell transplantation (allo‐HSCT) , but the details are not fully understood.…”
mentioning
confidence: 99%
“…10 Old age, total parenteral nutrition, low creatinine clearance, anemia, thrombocytopenia, organ failure, and shock were identified as major factors significantly associated with mortality in S. maltophilia BSI in different studies. 10,11 Though S. maltophilia causes infections in predominantly nosocomial settings, community-acquired infections are occasionally reported.…”
Section: Discussionmentioning
confidence: 99%